Implementation The Precautionary Principle For Land Deed Officials In Making Deeds Of Granting Mortgage Rights - Alvina Nur Aziziyah; J. M. Atik Krustiyati (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
PPAT in carrying out legal actions must always act carefully. PPAT before making a deed, must examine all relevant facts in its considerations based on applicable laws and regulations. This study aims to determine the application of the principle of caution of PPAT in making APHT and to determine the responsibility of PPAT in making APHT whose formal requirements are not met. This study is an empirical juridical legal study, namely legal research on the implementation of normative legal provisions in real behavior in legal events that occur. The results of the study explain that PPAT must apply the principle of caution and pay attention to the procedures in making APHT, as per Article 10 of the Mortgage Law. If PPAT is not careful in checking important facts, it means that PPAT violates the Principle of PPAT caution only explained in Article 22 of PP PPAT that the PPAT Deed must be read/explained to the parties in the presence of at least 2 (two) witnesses before being signed immediately by the parties, witnesses and PPAT. PPAT is personally responsible for the implementation of his duties and positions in every deed, including making APHT. Therefore, the role of PPAT in making APHT for creditors and debtors is to bridge the interests of debtors with the interests of creditors so that both parties get a sense of justice, benefit, and legal certainty in binding the Mortgage Right guarantee so that there are no legal defects.